Inspecting the impact of Big Five traits on internship stress and students’ rethinking stress - Hoang, Hai The; Nguyen, Phuoc-Thien; Luu, Ky; Tran-Thien, Gia-Phuoc; Tran-Chi, Vinh-Long (International Journal of Innovative Research and Scientific Studies, 2024)
This study aims to investigate the factors that contribute to internship stress among Vietnamese students by analyzing the associations between personality traits, internship stress, stress mindset, and demographics. A cross-sectional study design was utilized, comprising 149 Vietnamese students who were engaged in internship programs. The data gathering process encompassed the assessment of personality traits, internship stress levels, stress mindset, and participant demographics, which encompassed gender, age, GPA, and internship hours. We conducted path analyses to examine the relationships between these variables, and conducted moderation analyses to explore the interaction between age and the impact of extraversion on internship stress. Increased degrees of neuroticism were associated with a negative stress mindset, and this association was largely mediated by the stress experienced during an internship. Age moderated the negative association between the trait of extraversion and internship stress. More precisely, the association between extraversion and stress was significantly greater among younger students than it was among older students. Female students reported a lower stress mindset compared to male students, and higher GPAs were associated with both reduced internship stress and a more optimistic stress mindset. The results indicate that specific personality traits, such as neuroticism and extraversion, as well as internship stress, have a notable impact on the stress mindset of Vietnamese students. Gaining insight into these aspects can guide the development of internship programs that provide greater support and equip students with specific coping methods to enhance their well-being and manage internship difficulties more efficiently.